ANALISIS KINERJA MESIN PERCETAKAN DENGAN METODE FMEA DAN OEE PADA DIVISI PRINTING - Kusuma Putri, Alifia Panny; Ahmad; Saryatmo, M Agung (Jurnal Mitra Teknik Industri, 2023)
Printing machine is a tool for the process of transferring images for the printing industry. The machines studied at this company are the GTO 52, MO 65, and GTO 4W engines. Production will be problematic when there are many failure factors that affect machine performance and result in reduced productivity results. As in March, the total downtime of printing machines reached 1,067 minutes, while the rejects were 13,559 pcs. This is because the company also does not have proper maintenance implementation so that operators must be alert. Therefore, this study aims to carry out a comparative analysis of the effectiveness and determine the failure potential of each machine owned by this company using the FMEA and OEE methods. Based on the implementation results, it can be seen that the potential for failure occurs due to machine handling which must be improved through scheduling or periodic checking in order to reduce the hazard from the impact of machine conditions, product quality and increase the efficiency of printing machines. Meanwhile, the OEE value for April 2022 of the three machines produced 30.87% on the GTO 52 and 39.78% on the MO 65, which means that the effectiveness value is lower than the GTO 4W engine of 200.85%. The results of other months are still experiencing irregular increases and decreases, which means that the three machines need the right handling to be able to produce high OEE values ​​so that their operations are more efficient.